Using different art forms to investigate the impact on children's involvement in literacy activities. Issue 6 (18th August 2019) - Theodotou, Evgenia
ABSTRACT: Much of the research into factors that affect children's school performance has focused on parental involvement rather than the nature of children's activities undertaken in school. More research is therefore needed to examine the kinds of activities that affect performance and, in particular, whether the degree of involvement children experience in those activities can affect school performance. Children in free play often choose to be involved in arts activities so the arts could be considered as a promising approach. The purpose of this paper is to investigate the effects of 'Play and Learn through the Arts' programme on children's involvement during literacy activities in five- to six-year-old children. It was examined if the arts in general or a specific art form could contribute more to children's involvement in literacy activities. Children from four different settings participated in this study. To measure the outcome of the intervention the LIS-YC was used and items such as children's concentration, persistence and precision were measured. The findings were analysed using a mixed method approach and showed significant benefits in all the items in children's levels of involvement in the arts group over the control group and no difference in effects among the different art forms.